A Review of the Broken Hill Lead-Silver-Zinc Industry (The Australasian Institute of Mining and Metallurgy, 1940)
Before presentIng my address I wish to acknowledge the honour which has been conferred on me by my appointment to the position of President of the Australasian Institute of Mining and Metallurgy.It is a matter of great concern to us all to find our Empire at war. I am confident that, as was the case in the war of 1914-1918, members of this Institute and of kindred Institutes and Associations will contribute in full to the Empire's needs and that in the end our cause shall triumph.I think it appropriate that I should take as the subject of my address that of the Broken Hill Lead-Silver-Zinc Industry. The subject matter of this address has been confined to the operations of Mining, Ore Dressing, Lead Smelting and Refining and production of Electrolytic Zinc in Australasia. The review of the Broken Hill Lead-SilverZinc Industry would not, of course, be complete without reference to those Australian industries which trace their origin to the Broken Hill field, but· it is thought that an outline of these industries would make thIs review too extensive.HISTORICALMany efforts have been made to translate the early history of Broken Hill and its subsequent growth throughout the years into one of the wor~d's most famous mining fields in the form of a simple story.